Optimalisasi Manajemen Sarana Dan Prasarana Berbasis Green Education Dalam Mendukung Strategi Sekolah Ramah Lingkungan Di Sdn Sumber Wetan 2 Probolinggo - Putri Amelia; Mohamad Ahyar Ma’arif; Hemas Haryas Harja Susetya (JURNAL MANAJEMEN PENDIDIKAN, 2026)
Optimization of Green Education-Based Facilities and Infrastructure Management in Supporting the Environmentally Friendly School Strategy at SDN Sumber Wetan 2 Probolinggo This study aims to describe and analyze the implementation of optimizing the management of facilities and infrastructure based on green education, formulate the applied strategies, and explain the implications of such management in supporting the realization of an eco-friendly school at SDN Sumber Wetan 2 Probolinggo. The method employed is qualitative research with a descriptive approach, where data collection is carried out through in-depth interviews, direct observation, and documentation studies, while data analysis is conducted through stages of reduction, data presentation, and conclusion drawing. The results show that the management of facilities and infrastructure implemented includes the stages of planning, procurement, utilization, maintenance, and disposal, which have begun to be integrated with the principles of environmental education, although the implementation has not yet been fully optimal due to limitations in facilities that meet national standards. School strategies are focused on improving the efficiency of resource use, organizing green open spaces, and instilling environmentally friendly behavior through the management of school facilities. The implications of this management are evident in the establishment of a healthier learning environment, the growing awareness among school members, and tangible support for eco-friendly school policies. It is concluded that the optimization of facilities and infrastructure management based on green education serves as an effective and strategic foundation in realizing a school that not only meets educational standards but also possesses character, sustainability, and environmental friendliness.